Pharmacists' perceptions of advancing public health priorities through medication therapy management - Casserlie LM; DiPietro Mager NA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2016)
Background: Public health priorities can be addressed by pharmacists through channels such as medication therapy management (MTM) to optimize patient and population outcomes. However, no studies have specifically assessed pharmacists' perceptions of addressing public health priorities through MTM. Objective: The objective of this study was to assess pharmacists' opinions regarding the feasibility and appropriateness of addressing seven areas of public health priority through MTM services to impact public health in direct patient care settings. Methods: An anonymous 37-question electronic survey was conducted to evaluate Ohio pharmacists' opinions of advancing seven public health priorities identified from Healthy People 2020 (family planning, preconception care, smoking cessation, immunizations, nutrition/biometric wellness assessments, point-of-care testing, fall prevention) through MTM activities; to identify potential barriers; and to collect demographic information. The cross-sectional survey was sent to a random sample of 500 pharmacists registered with the Ohio State Board of Pharmacy. Results: Seventy-six pharmacists responded to the survey, resulting in a 16% response rate. On average, it took respondents 5-10 minutes to complete the survey. The majority of respondents thought that each of the seven public health priorities were "important" or "very important" to patient health; the most commonly identified areas included smoking cessation, immunizations, and fall prevention (97.5%). When asked to indicate which of the seven areas they thought they could potentially have a role to provide services through MTM, on average pharmacists picked 4 of the priority areas. Only 6.6% indicated there was no role for pharmacists to provide MTM services for any of the listed categories. Staffing, time, and reimbursement represented the most commonly perceived barriers for pharmacists in providing MTM services. Fifty-seven percent indicated an interest in learning more about MTM, with 98% of responders selecting continuing education as the preferred source. Conclusion: The majority of pharmacists indicated they could make an impact on public health priorities through MTM services.